2022
DOI: 10.3390/ijerph19031762
|View full text |Cite
|
Sign up to set email alerts
|

Resilience during Crisis and the Role of Age: Involuntary Telework during the COVID-19 Pandemic

Abstract: We investigated the relationship between age, resilience, job demands and resources, and self-regulation in 1715 university employees during the COVID-19 pandemic (February 2021) by means of an online survey with closed and open questions. Correlation, regression, and qualitative analyses showed that older employees reported higher resilience than younger employees. This finding was robust after controlling for background factors (i.e., gender, expat status, job type, living alone). Age and resilience were dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 57 publications
0
33
0
7
Order By: Relevance
“…A recent meta-analysis also found that anxiety levels were consistently associated with younger age during the pandemic [57]. This could be explained by the relationship between resilience and anxiety among COVID-19 patients, with older subjects showing higher levels of resilience [58][59][60].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent meta-analysis also found that anxiety levels were consistently associated with younger age during the pandemic [57]. This could be explained by the relationship between resilience and anxiety among COVID-19 patients, with older subjects showing higher levels of resilience [58][59][60].…”
Section: Discussionmentioning
confidence: 95%
“…This could be explained by the relationship between resilience and anxiety among COVID-19 patients, with older subjects showing higher levels of resilience [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…The novel coronavirus, also known as COVID-19, is a highly transmittable and pathogenic disease [ 1 ]. It has instigated fear and caused panic all over the globe [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], negatively affected public health, crippled economies, and transformed social and business environments [ 16 ]. The COVID-19 pandemic, which is regarded as one of the worst pandemics in human history [ 17 ], has also had an unprecedented effect on the living conditions and deaths of human beings.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we examined family contexts involving a new model of living in which several members are adapted to home confinement, with online work and school activities in the same space and at the same time. Sleep has been addressed considering the impact of telework and age/gender differences [ 5 , 7 , 12 , 13 ], but the evidence is still poor.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the family context and work at home, the literature suggests that women and men behaved differently in terms of telework before the pandemic outbreak [ 12 ]. Women face less autonomy with remote work due to family constraints and the more roles they play in family tasks (working at home full-time).…”
Section: Introductionmentioning
confidence: 99%